Knowledge And Awareness Of Muslim Consumers Towards Gelatine Existence In Halal Pharmaceutical Products: A Case Study Of Duopharma Bangi - Othman, Muhammad Ikmal Haaziq; Abdul Rasol, Lokman; Ibrahim, Nurshahira; Bin Ibrahim, Rasyad Afif; Che Hassan, Nurul Hidayah; Md Baharudin, Md Hamzaimi Azrul (Journal of Islamic, Social, Economics and Development, 2025)
This study investigates the knowledge and awareness levels of Muslim consumers regarding the presence of gelatin in pharmaceutical products, specifically focusing on employees at Duopharma Bangi, Malaysia. Gelatin, commonly derived from animal sources including non-halal ones, poses significant religious concerns for Muslim consumers. Through a quantitative approach using survey methodology, data was collected from 150 Muslim respondents working in various departments at Duopharma. The findings revealed that while respondents demonstrated a moderate to high level of knowledge about gelatin in pharmaceuticals (mean scores ranging from 3.66 to 4.16), their awareness of its implications was even higher (mean scores ranging from 4.15 to 4.55). The study highlights the importance of transparent labeling, regulatory oversight, and consumer education in ensuring Muslim consumers can make informed choices aligned with their religious requirements. These findings have implications for pharmaceutical manufacturers, regulatory bodies, and Muslim consumers navigating the complex landscape of halal pharmaceutical products.